The Monster Theory Reader - Weinstock, Jeffrey Andrew (Book collections on Project MUSE., 2020)
Keeping pace with Western culture's fascination with monsters, monster theory has attempted to explore the significance of monsters in different genre, media, and cultural contexts; complicating this project however has been the absence of a single volume collecting in one place central approaches and significant works. This book brings together some of the scattered articles, essays, and book chapters theorizing monsters and monstrosity, thereby making the volume useful for researchers and ideal for course adoption for classes involving a focus on monsters."